A Comparative Study of Three Different Types of Stem Cells for Treatment of Rat Spinal Cord Injury. Issue 4 (April 2017) - Ruzicka, Jiri; Machova-Urdzikova, Lucia; Gillick, John; Amemori, Takashi; Romanyuk, Nataliya; Karova, Kristyna; Zaviskova, Kristyna; Dubisova, Jana; Kubinova, Sarka; Murali, Raj; Sykova, Eva; Jhanwar-Uniyal, Meena; et al.
Three different sources of human stem cells—bone marrow-derived mesenchymal stem cells (BM-MSCs), neural progenitors (NPs) derived from immortalized spinal fetal cell line (SPC-01), and induced pluripotent stem cells (iPSCs)—were compared in the treatment of a balloon-induced spinal cord compression lesion in rats. One week after lesioning, the rats received either BM-MSCs (intrathecally) or NPs (SPC-01 cells or iPSC-NPs, both intraspinally), or saline. The rats were assessed for their locomotor skills (BBB, flat beam test, and rotarod). Morphometric analyses of spared white and gray matter, axonal sprouting, and glial scar formation, as well as qPCR and Luminex assay, were conducted to detect endogenous gene expression, while inflammatory cytokine levels were performed to evaluate the host tissue response to stem cell therapy. The highest locomotor recovery was observed in iPSC-NP-grafted animals, which also displayed the highest amount of preserved white and gray matter. Grafted iPSC-NPs and SPC-01 cells significantly increased the number of growth-associated protein 43 (GAP43 + ) axons, reduced astrogliosis, downregulated Casp3 expression, and increased IL-6 and IL-12 levels. hMSCs transiently decreased levels of inflammatory IL-2 and TNF-α. These findings correlate with the short survival of hMSCs, while NPs survived for 2 months and matured slowly into glia- and tissue-specific neuronal precursors. SPC-01 cells differentiated more in astroglial phenotypes with a dense structure of the implant, whereas iPSC-NPs displayed a more neuronal phenotype with a loose structure of the graft. We concluded that the BBB scores of iPSC-NP- and hMSC-injected rats were superior to the SPC-01-treated group. The iPSC-NP treatment of spinal cord injury (SCI) provided the highest recovery of locomotor function due to robust graft survival and its effect on tissue sparing, reduction of glial scarring, and increased axonal sprouting.